Study protocol to investigate the environmental and genetic aetiology of atopic dermatitis: the Indonesian Prospective Study of Atopic Dermatitis in Infants (ISADI). Issue 3 (3rd March 2017) - Tanjung, Conny; Rzehak, Peter; Mansyur, Muchtaruddin; Munasir, Zakiudin; Sudoyo, Herawati; Immanuel, Suzanna; Irawan, Roedi; Reischl, Eva; Demmelmair, Hans; Koletzko, Berthold; Hadinegoro, Sri Rezeki; Sjarif, Damayanti Rusli
Abstract : Introduction: Atopic dermatitis (AD) is the most common skin disorder in young children worldwide, with a high impact on morbidity and quality of life. To date, no prospective study has been published on the incidence and potential predictors of AD in South East Asian populations. The Indonesian Prospective Study of Atopic Dermatitis in Infants (ISADI) will address the genetic, metabolic and dietary characteristics of mothers and their offspring, as well as potential determinants of AD within the first year of infant life. Methods and analysis: This prospective study will be undertaken in about 400 infants to investigate the direct and indirect effects of filaggrin ( FLG ) gene mutations, the genetic variants of FADS1, FADS2 and FADS3 and the role of long-chain polyunsaturated fatty acids (LCPUFA) on the development of AD. We will use standardised protocols for subject recruitment, umbilical artery plasma analysis, buccal cell sampling for genotyping, fatty acid analysis, physical exams, 3-day food-intake recall of mothers and children, as well as comprehensive questionnaires on environmental, socioeconomic and AD-related factors, including family history. Monthly monitoring by telephone and physical exams every 3 months will be carried out to assess participants' anthropometry, medical history and incidence of AD diagnosis during the first year of life. Hypotheses-driven analyses of quality-controlled dietary, genetic and metabolic data will be performed with state-of-the-art statistical methods (eg, AD-event history, haplotype, dietary or metabolic factor analysis). Direct and indirect effects of genetics and LCPUFA in buccal cell and cord plasma glycerophospholipids as potential mediators of inflammation on AD development will be evaluated by path analysis. Ethics and dissemination: The Permanent Medical Research Ethics Committee in Medicine and Health/Faculty of Medicine Universitas Indonesia/Dr Cipto Mangunkusumo Hospital (No. 47/H2.F1/ETIK/2014) approved the study protocol (extended by the letter no. 148/UN2.F1/ETIK/2015). We aim to disseminate our findings via publication in an international journal with high impact factor.